Isolation and Genetic Identification of Endophytic Lactic Acid Bacteria From the Amazonian Açai Fruits: Probiotics Features of Selected Strains and Their Potential to Inhibit Pathogens - Abe Sato, Suenne Taynah; Marques, Joana Montezano; da Luz de Freitas, André; Sanches Progênio, Raphaela Cristina; Nunes, Márcio Roberto Teixeira; Mota de Vasconcelos Massafra, Janaína; Gomes Moura, Fábio; Rogez, Hervé (Frontiers in Microbiology, 2021)
The açai palm (Euterpe oleracea) is native to the Amazon basin, a humid tropical forest. High levels of total mesophilic bacteria with high diversity have been consistently reported in açai fruits. As local consumers have few digestive problems, the results of the present study reveal the lactic acid bacteria (LAB) recovered from açai fruits with characteristics that suggest they are possible candidates for probiotics and antagonistic potential against pathogens for the first time. Açai fruits were sampled from five different locations in the Eastern Amazonia floodplains. Sixty-six isolates were recovered from fruits and tested for some probiotic characteristics following FAO/WHO guidelines. Approximately 65% of the isolates showed no catalase or oxidase activity, Gram-positive staining or cocci and bacilli cell morphology. Furthermore, 48% of the isolates demonstrated preliminary characteristics that suggest safety for use, as they presented no coagulase enzyme activity or gamma-hemolysis. These strains were identified as belonging to the genera Lactiplantibacillus and Pediococcus, and 32 strains also presented resistance to vancomycin, ciprofloxacin and streptomycin. In addition, 28 isolates showed a survival rate, expressed as log cycle reduction, higher than 0.9 under gastric conditions (pH 2). All strains tested positive in bile salts deconjugation tests and showed a survival rate higher than 0.8 in the presence of this salt. Regarding antimicrobial activity against pathogens, all strains were able to inhibit Salmonella Typhimurium (ATCC® 14028™) and 97% were capable of inhibiting Escherichia coli (ATCC® 25922™). Concerning the results of in vitro antagonistic assays, three isolates (B125, B135, and Z183 strains) were selected for antagonistic tests using açai juice contaminated with these two pathogens. All tested LAB strains were able to inhibit pathogen growth in açai juice. In summary, açai fruits are a potential source of LAB isolates to be investigated as probiotics.